The Influence of Viral Marketing and Brand Awareness on Consumer Purchase Intentions for Mixue Beverage Products in Malang - Broto, Felik Sad Windu Wisnu; Karnalim, Teofilus; Anastasia, Monica (International Journal of Business and Applied Economics, 2024)
In the current digital era, viral marketing and brand awareness have become crucial strategies for companies to increase sales and attract consumer interest. This study aims to examine the impact of viral marketing and brand awareness on the purchase intentions of Mixue beverage consumers in Malang. The research employs a quantitative approach, collecting data through surveys using questionnaires distributed to Mixue consumers in Malang. The data analysis results show that viral marketing has a significant positive effect on the purchase intentions of Mixue consumers in Malang. The higher the intensity of viral marketing, the greater the consumers' purchase intentions. Additionally, brand awareness also has a significant positive impact on purchase intentions. Consumers with high brand awareness tend to have higher purchase intentions for Mixue products. Simultaneous analysis indicates that viral marketing and brand awareness together significantly affect consumer purchase intentions. Therefore, it is essential for Mixue in Malang to effectively enhance viral marketing and brand awareness strategies to boost consumer purchase intentions. These strategies have proven effective in increasing the sales of Mixue products in Malang.